Convergence of illuminating beams suffering from scattering during the individual measurement of suspended particles - Li, Jiajin; Deng, Hanbo; Guo, Zhiming; Liao, Ran; Ma, Hui (Frontiers in Physics, 2022)
The convergent illuminating beam is the key factor during the individual measurement of suspended particles in aquatic suspension. When the illuminating beam propagates in the suspension, the particulate scattering in the optical path may destroy the convergence of illuminating beam, especially in the suspensions with high particulate concentration. In this paper, using the Monte Carlo simulation, the convergence of the illuminating beam is investigated by changing the physical properties of particles such as size and concentration, and the optical path length of the illuminating beam. A dimensionless quantity, as the product of the scattering coefficient of suspension and the optical path length, is found to determine the achievement of convergent beam. Moreover, an individual measurement setup based on the convergence of the illuminating beam is used to measure polystyrene microspheres with different concentrations. The experiment results are consistent with those of the simulations. Further, improvement strategies are proposed and proved to effectively keep the convergence of the illuminating beam in turbid water. Results in this work can provide clues for designing similar optical apparatus used in the aquatic environment monitoring.